Retinal microvasculature alteration in patients with acute pancreatitis: an observational OCTA study - Xian-Zhe Qian; Jin-Yu Hu; Yan-Mei Zeng; Hong Wei; Xiao-Yu Wang; Cheng Chen; Qian-Min Ge; Jie Zou; Xian-Mei Zhou; Qian Ling; Liang-Qi He; Xuan Liao; et al. (European Journal of Medical Research)
Abstract Objective To evaluate changes in retinal layer thickness and microvascular density in pancreatitis patients using optical coherence tomography angiography (OCTA). Methods The study involved 16 pancreatitis patients and 16 healthy controls. Each participant underwent a superficial OCTA scan, with images divided into nine subregions to compare macular retinal thickness (RT) and superficial vascular density (SVD) between groups. Results Pancreatitis patients exhibited reduced retinal thickness in specific macular areas, including inner, full, and outer layers (p < 0.05). Additionally, decreased superficial vascular density was noted in inner superior (IS), outer superior (OS), inner nasal (IN), and outer nasal (ON) regions (p < 0.05). ROC curve analysis showed high diagnostic accuracy for full-layer inner superior, outer superior, and outer inferior thickness with areas under the curve of 0.9429, 0.9233, and 0.9990, respectively. Conclusions Pancreatitis is associated with macular retinal thinning and decreased superficial vascular density, offering potential for improved diagnostic imaging.